Occurrence of Megaselia scalaris Loew (Diptera: Phoridae) in Mischocyttarus cassununga Von Ihering (Hymenoptera: Vespidae: Polistinae) nests - Sheliane Cristina Coelho Francisco; Gabriel de Castro Jacques; Luís Cláudio Paterno Silveira (EntomoBrasilis, 2022)
Social wasp nests create an environment rich in resources, such as food and shelter, which consequently attract predators, parasites, and parasitoids. Parasitoids attacks can be one of the main causes of mortality among social wasps in the early stages of development. Therefore, the aim of this work is to report the occurrence of parasitoids in Mischocyttarus cassununga Von Ihering (Hymenoptera: Vespidae: Polistinae) nests, in an area of Cerrado, at the Federal Institute of Education, Science and Technology of Minas Gerais (IFMG) - Campus Bambuí, Brazil. There was an emergence of four parasitoids from two nests of M. cassununga, identified as Megaselia scalaris (Loew) (Diptera: Phoridae), the first record of this parasitoid in M. cassununga in a Cerrado area.